Modelli semplificati di analisi delle sorgenti di rischio e del sovraccarico biomeccanico nel settore artigiano: esperienze applicative nel comparto dei baristi / Simplified models of analysis of the sources of risk and biomechanical overload in the small industries sector: experience of application among bartenders - Ardissone, S. (La Medicina del Lavoro, 2011)
«Simplified models of analysis of the sources of risk and biomechanical overload in the small industries sector: experience of application among bartenders». Background: Over the last 20 years, the café/snackbar sector has undergone a substantial development in Italy, expanding all over the country via countless small businesses, with other larger businesses springing up especially along major communication routes; thousands of workers are employed in this sector today. The safety issues and health risks involved in working in this type of service industry are often underestimated, with the risk that accidents and diseases of occupational origin may occur among the employees, particularly skeletal-muscular disorders. Objectives and methods: The study, which was carried out on the premises of a major operator, applies the method of “pre-mapping” of risk, herein described, which can identify the presence or absence of occupational risks and any need for further evaluation. Conclusion: The results of the study revealed the existence of health risks for the workers: in addition to the traditional risks there were also biomechanical  and organizational hazards.